f and g are functions defined as f ( x ) = 5 x + 2 x − 2 6 and g ( x ) = 3 x − 2 4 x . What is the value of ( f ∘ g ) ( 4 ) ?
Note: f ∘ g denotes the composition of the 2 functions.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
thnx
We've the values of f(x) & g(x): Now, we got to solve f o g ( 4 ) , If we simplify this term a li'l bit, we get: f ( g ( x ) ) where x=4 .
First Step: Solve the g(x) for x=4 : 3 × 4 − 2 4 × 4 = 5 8
Second Step: solve f(x) for x=8/5 : 5 × 5 8 + 2 × 5 8 − 2 6
on further solving we get: 8 + 5 = 1 3 .
So, our answer is 13.
can we substitute 4 after substituting the g(x) in f(x)
thnx
g ( x ) = 3 x − 2 4 x
g ( 4 ) = 3 ( 4 ) − 2 4 ( 4 )
which simplifies to 5 8
f ( x ) = 5 x + 2 x − 2 6
f ( 5 8 ) = 5 ( 5 8 ) + 2 ( 5 8 ) − 2 6
which simplifies to 8 + 5
that gives an answer of 1 3
fog(4)=f(g(4))
g(4)=4(4)/(3(4)-2)=8/5
f(8/5)=..... =13
Problem Loading...
Note Loading...
Set Loading...
( f o g ) ( x ) = f ( g ( x ) )
g ( 4 ) = 5 8
f ( 5 8 ) = 8 + 5 = 1 3